2021
DOI: 10.1111/jcal.12543
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between language learners and teachers concerns about emergency remote teaching

Abstract: Emergency remote teaching refers to the unanticipated, involuntary shift to a virtual learning environment due to, for example, a natural disaster or political instability. The sudden nature of this transition creates additional challenges to effective learning. In this article, we investigate one such challenge, namely the potential for teacher–student miscommunication. We report on a study involving 674 language learners and 61 language teachers. The participants were asked to rate a number of education‐rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 48 publications
2
28
1
Order By: Relevance
“…On the other hand, studies about ERT are still growing because it is the first time in history to have a long emergency shift to distance learning. Moreover, some recent studies about ERT showed that most courses and plans were not well developed (Hakami, 2020;Johnson, Veletsianos, & Seaman, 2020;Al Shlowiy et al, 2021). Therefore, this study attempted to fill in the gap by focusing on the acceptance and perceptions of ERT for a long time that includes three semesters.…”
Section: Related Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, studies about ERT are still growing because it is the first time in history to have a long emergency shift to distance learning. Moreover, some recent studies about ERT showed that most courses and plans were not well developed (Hakami, 2020;Johnson, Veletsianos, & Seaman, 2020;Al Shlowiy et al, 2021). Therefore, this study attempted to fill in the gap by focusing on the acceptance and perceptions of ERT for a long time that includes three semesters.…”
Section: Related Literaturementioning
confidence: 99%
“…Although there are benefits of online learning systems, research shows some issues, such as the issues of internet connection (Alshehri & Cumming, 2020), personal devices issues (Hakami, 2020), students' privacy issues (Sharma, 2019), screen issues (Oyaid & Alshaya, 2019), and technical issues (Al Shlowiy et al, 2021). Moreover, some teachers have negative perceptions of using online learning so that they do not effectively employ its methods in their teaching experiences.…”
Section: Related Literaturementioning
confidence: 99%
See 3 more Smart Citations